RANCANG BANGUN SISTEM INFORMASI MANAJEMEN MAGANG MAHASISWA BERBASIS WEB DENGAN MENGGUNAKAN FRAMEWORK LARAVEL - Muhammad Nugraha; Ricak Agus; Halimil Fathi; Rizki Baginda (Journal of Information Technology and Its Utilization, 2023)
In this research, the author will discuss the development of a student internship information system implemented using the Laravel framework. The aim is to provide convenience for students in registering/applying for internships, reporting daily activities, submitting final reports, and updating all other internship-related information, as well as facilitating institutions in managing internship data. The method used in this research is the information system development method, which includes literature review, needs analysis, system design, testing, and evaluation. The Laravel framework was chosen because of its good performance, ease of use, and many features that can facilitate the development of information systems. The student internship management information system designed has easy-to-use internship registration and reporting features that can be accessed from anywhere, as well as integrated internship data management features. The results of this research show that the development of a student internship information system using the Laravel framework can provide convenience in registering and reporting internship results for students, as well as help institutions in managing internship data. It is hoped that with the existence of this student internship information system, it can be a solution to simplify and accelerate the internship process and management for students and participating institutions.